GUIDELINES FOR BUILDING RELATIONSHIP THE COMMUNITY BY USING THE PRINCIPLES OF SARANEEDHARMA 6 OF BAN KHOK SAI SCHOOL UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Suvanburee, Arunrat (Journal of MCU Nakhondhat, 2023)
The objectives of this research are: 1) to study the condition of building relationships with the community. 2) to study guidelines to build community relations according to the Saraneedharma 6 to study the guidelines to build community relations according to the Saraneedharma 6. 3) to present the guidelines for building relationships with communities according to the Saraneedharma 6. This research is qualitative research. The data were collected through in-depth interviews with 15 people. 5 key informants and a focus group of 7 experts. The statistic used content analysis. The results showed that; 1. The condition of building relations with the community consists of 7 factors as follows: 1) School policies 2) Readiness of schools and communities 3) Cooperation from all parties 4) Mechanisms that lead to cooperation 5) Establish a basic education committee, Parent-teacher associations 6) Define common roles and responsibilities in the desired direction; and 7) Operate for cooperation. 2. The result of Guidelines for building relationships with the community according to the Saraneedharma 6, there are 7 factors as follows: 1) School policies 2) Readiness of schools and communities 3) Cooperation from all parties 4) Mechanisms that lead to cooperation 5) Establish a basic education committee, Parent-teacher associations 6) Define common roles and responsibilities in the desired direction; and 7) Operate for cooperation. All steps are carried out together using the Saraneedharma 6 principles. 3. The experts verified the guidelines to build community relations according to the Saraneedharma 6 and found that regarding the focus group discussion, the guidelines have suitable, possibility, and usefulness which can be applicable in daily life.